The Effect of Consuming Katuk Leaf Shoots on Hb Levels of TM II Pregnant Women at the Primary Health Care Lemo - Dewi Royani; Widia Shofa Ilmiah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Anemia in pregnancy is a global health problem that can affect the condition of the mother and fetus, especially with its prevalence still high in developing countries. Katuk leaves, which are known to contain iron and various bioactive compounds, are seen as having potential as an alternative to help increase hemoglobin levels in pregnant women. This study aims to analyze the effect of consuming katuk leaf shoots on the Hb levels of pregnant women in the second trimester at the UPT Primary Health Care Lemo using a one-group pretest–posttest quasi-experimental design. The research population was all second trimester pregnant women with a sample of 35 respondents selected purposively based on inclusion criteria. Hb levels were measured before and after the intervention, then analyzed using the Wilcoxon signed-rank test. The results showed a Z value = -5.385 with p value = 0.000 (p < 0.05), which indicates a significant difference between Hb levels before and after consuming katuk leaf shoots. Thus, consumption of katuk leaf shoots was proven to have a significant effect in increasing the Hb levels of second trimester pregnant women at the UPT Primary Health Care Lemo.